LAS ARQUITECTURAS IMAGINARIAS DE EMILIO ADOLFO WESTPHALEN - Miranda Lévano, Sylvia (2010)
This article examines the relationships between literature and architecture in some or Emilio Adolfo Westphalen´s poetic texts. By analyzing these texts we can observe the points or contact between both subject matters, which are conceptualized, from a literary perspective, as imaginary architectures. We lay bare the intrinsic union between Daedalus and Orpheus; that is to say, between the technical forces that create life on earth and the poetic chant, between the ways to either inhabit the world or to name it. In so doing, we put forth the capability of Westphalen 's poetry to question a coarse and hostile reality by introducing other possible worlds.